Anti-inflammatory and immunoregulatory effects of pinolenic acid in rheumatoid arthritis. (3rd June 2021) - Takala, Rabaa; Ramji, Dipak P; Andrews, Robert; Zhou, You; Burston, James; Choy, Ernest
Abstract: Objectives: In pre-clinical studies, pinolenic acid (PNLA), an omega-6-polyunsaturated fatty acid from pine nuts, has shown anti-inflammatory effects. We aimed to investigate the effect of PNLA in human cell lines and peripheral blood mononuclear cells (PBMCs) from RA patients and healthy controls (HCs). Methods: A modified Boyden chamber was used to assess chemokine-induced migration of THP-1 monocytes. Macropinocytosis was assessed using Lucifer yellow and oxidized low-density lipoprotein (oxLDL) uptake using DiI-labelled oxLDL in THP-1 macrophages and human monocyte-derived macrophages (HMDMs). IL-6, TNF-α and prostaglandin E2 (PGE2) release by lipopolysaccharide (LPS)-stimulated PBMCs from RA patients and HCs was measured by ELISA. The transcriptomic profile of PNLA-treated, LPS-activated PBMCs was investigated by RNA-sequencing. Results: PNLA reduced THP-1 cell migration by 55% ( P  < 0.001). Macropinocytosis and DiI-oxLDL uptake were reduced by 50% ( P  < 0.001) and 40% ( P  < 0.01), respectively, in THP-1 macrophages and 40% ( P  < 0.01) and 25% ( P  < 0.05), respectively, in HMDMs. PNLA reduced IL-6 and TNF-α release from LPS-stimulated PBMCs from RA patients by 60% ( P  < 0.001) and from HCs by 50% and 35%, respectively ( P  < 0.01). PNLA also reduced PGE2 levels in such PBMCs from RA patients and HCs ( P  < 0.0001). Differentially expressed genes whose expression was upregulated included pyruvate dehydrogenase kinase-4, plasminogen activator inhibitor-1, fructose bisphosphatase1 and N-Myc downstream-regulated gene-2, which have potential roles in regulating immune and metabolic pathways. Pathway analysis predicted upstream activation of the nuclear receptors peroxisome proliferator-activated receptors involved in anti-inflammatory processes, and inhibition of nuclear factor-κB and signal transducer and activator of transcription 1. Conclusions: PNLA has immune-metabolic effects on monocytes and PBMCs that are pathogenic in RA and atherosclerosis. Dietary PNLA supplementation may be beneficial in RA.